Smart Grid Study As Solution To The Challenges Of Electricity Transmission And Distribution In North Sulawesi - I Gede Budi Mahendra; Djubir R.E. Kembuan; Janne Deivy Ticoh; Billy Killis; Djami Olii (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Electricity delivery in North Sulawesi faces many problems, such as inadequate supply, unreliable infrastructure, ineffective power transfer, and inadequate integration of renewable sources. This research is a literature study that provides a logical description in accordance with the study objectives. The results of this study show that Smart Grid Technology is considered a feasible solution to overcome the problem. Smart Grid can revolutionize the power grid in this region by monitoring and controlling superior power transmission by combining contemporary information and communication technology with conventional energy infrastructure. As this research shows, Smart Grid solutions can improve the efficiency and reliability of electric power transmission and distribution in North Sulawesi.